Late-arriving 2023 summer marine heatwave in the East China Sea and implications for global warming - Hyoeun Oh; Jung-Eun Chu; Yongchim Min; Go-Un Kim; Jongmin Jeong; Suchan Lee; Jaeik Lee; Jin-Young Jeong (npj Climate and Atmospheric Science)
Abstract In 2023, the global temperature rose significantly, triggering a marine heatwave (MHW) in the East China Sea (ECS) from August 12 to October 13. Unlike the typical July onset, this event was delayed. Here we investigate the mechanisms behind the late onset and prolonged duration of the 2023 MHW in the ECS and its potential linkage to global warming. The early phase was driven by shortwave radiation and ocean dynamics, while the later phase saw reduced northerly winds, allowing warmer, more humid southerlies to dominate. This shift decreased the air-sea humidity difference, enhancing downward latent heat fluxes. Future CMIP6 projections also suggest that delayed MHWs are linked to weak heat exchanges, limiting the oceanic heat transport to the atmosphere. Our findings highlight the increasing risk of prolonged MHWs in the ECS and the urgent need for improved climate preparedness.